P719 Symptomatic improvement and long-term stability of ulcerative colitis symptoms over 3 years of ozanimod treatment. (30th January 2023) - Danese, S; Abreu, M T; Afzali, A; Canavan, J B; Jain, A; Wu, H; Petersen, A; Panaccione, R; Wolf, D C
Abstract: Background: The phase 3 True North (TN) study demonstrated the efficacy and safety of ozanimod over 52 weeks in patients (pts) with moderately to severely active ulcerative colitis (UC). Pts completing 52 weeks of TN were eligible for the ongoing TN open-label extension (OLE) assessing the long-term efficacy and safety of ozanimod. Presented here is the interim analysis of the TN OLE focused on the symptomatic efficacy of ozanimod in pts with approximately 3 years of continuous ozanimod treatment. Methods: Pts who achieved clinical response after receiving 52 weeks of continuous ozanimod during TN and subsequently entered the TN OLE were evaluated (data cutoff: 10 January 2022, at which point the OLE Week 94 disposition was available for pts). Patient-reported (rectal bleeding subscore [RBS] and stool frequency subscore [SFS]) and clinician-reported (Physician's Global Assessment) symptomatic outcomes were determined. Symptomatic clinical response (partial Mayo score [PMS] ≥1 point and ≥30% reduction in PMS with ≥1-point decrease in RBS or absolute RBS of ≤1) and symptomatic clinical remission (RBS=0 and SFS ≤1 [and decrease of ≥1 point from baseline SFS]) were evaluated at OLE Week 5 through OLE Week 94 (146 weeks of continuous ozanimod treatment) using observed case (OC) and nonresponder imputation (NRI) analyses. PMS, RBS, and SFS were assessed from TN baseline to OLE Week 94. Results: In all, 131 pts entered the OLE after achieving clinical response following 52 weeks of continuous ozanimod during TN. At data cutoff, 87.0% completed OLE Week 46 (98 weeks of continuous ozanimod) and 71.8% completed OLE Week 94 (146 weeks of continuous ozanimod). Pts had a mean age of 44 years and 52% were female. Most (68%) had left-sided UC disease, 24% had concomitant corticosteroid use at TN baseline, and 32% had prior exposure to tumor necrosis factor inhibitors. Symptomatic clinical response and symptomatic clinical remission were observed in 100.0% (Figure 1A) and 84.4% (Figure 2A) of pts, respectively, at OLE Week 5 in the OC analysis (93.1% [Figure 1B] and 78.6% [Figure 2B] in the NRI analysis). Rates of symptomatic clinical response and symptomatic clinical remission were maintained through OLE Week 94 in the OC analysis and decreased slightly over time in the NRI analysis. Reductions in mean PMS from baseline were observed during TN and sustained through OLE Week 94. Reductions from TN baseline in RBS (Figure 3) and SFS (Figure 4) were also observed through OLE Week 94. Conclusion: This interim analysis of the TN OLE focusing on symptomatic endpoints found that most pts who achieved clinical response after 1 year of ozanimod sustained symptom control for another 2 years.